(untitled) (American Journal of Islam and Society, 1997)
Islam in West Africa is a collection of nineteen essays written by Nehemia Levtzion between 1963 and 1993. The book is divided into five sections. dealing with different facets of the history and sociology of Islam in West Africa. The first section focuses on the patterns, characteristics, and agents of the spread of Islam. The author offers an approach to the study of the process of that Islamization in West Africa that compares pattems of Islamizacion in medieval Mali and Songhay to patterns in the Volta basin from the seventeenth to the nineteenth centuries. He also assesses the complex roles played by African chiefs and kings and slavery in the spread of Islam. Section two focuses on the subject of lslam and West African politics from the medieval period to the early nineteenth century. Levtzion identifies two trend in African Islam: accommodation and militancy. Islam’s early acceptance in West African societies was aided by the fact that Islam was initially seen as a supplement, and not as a substitute, to existing religious systems. Levtzion analyzes the dynamics of Islam in African states as accommodation gave way in time to tensions between the ruling authorities and Islamic scholars, calling for a radical restructuring of the stare according to Islamic ideals. The tensions between the Muslim clerics of Timbuktu and the medieval Songhay rulers. and the ultimately adversarial relationship between Uthman dan Fodio and the Gobir leadership in eighteenth-century Hausaland, are singled out for sustained analysis ...